Peningkatan Keterampilan Berargumentasi Ilmiah Pada Siswa Melalui Model Pembelajaran Argument- Driven Inquiry (ADI) - Nasution, Eni Sumanti (JURNAL EKSAKTA PENDIDIKAN (JEP), 2019)
Destination of research to analyze increased  students' scientific argumentative ability by way of Argument-Driven Inquiry (ADI) learning model in SMA Negeri 1 Batang Angkola. The study was conducted in a quasi-experiment manner. As for population of the research was students of class X SMAN 1 Batang Angkola.  Sample selection that has been used by cluster random sampling, namely class X IPA1 and X IPA2. This research instrument uses a valid and reliable Learning Outcomes test. The data in this study were analyzed by T- test. The results of the study obtained differences in values of scientific argumentation skills in students through argument-driven inquiry learning model  at 76.6 and conventional learning 70.06, this means that there is an influence of students' scientific argumentation skills using the Argument Driven Inquiry learning model  more improved compared to using conventional learning.